Space frame- Pile foundation-soil interaction analysis - Dode, P.A.; Chore, H.S.; Upadhyay, D.K. Agrawal (Journal of Structural Engineering, 2025)
The study deals with physical modeling of a typical building frame supported by pile foundation using three dimensional finite elements. The foundation comprises of pile group having four piles (2 × 2 arrangement) and embedded in cohesive soil mass. For the purpose of modeling, the elements of the superstructure frame such as beams, columns and slab; and that of the pile foundation such as pile and pile cap are descretized using twenty noded isoparametric continuum element. The interface between the pile and the soil is idealized using sixteen node isoparametric surface element. The more refined finite element mesh is used in the present study for modeling soil element as compared to the one used in the similar study reported in the literature (Chore and Ingle 2008). Three different elements are used for discretizing the soil. The soil elements are modeled using eight node, nine node and twelve nod continuum elements. The present study considers the linear elastic behaviour of the superstructure and substructure (i.e., foundation) elements including that of soil. Further, the immediate behaviour of the soil is considered and total stresses in soil are considered. The parametric study is carried out for studying the effect of soil- structure interaction on response of the frame. The frame is analyzed initially without considering the effect of the foundation and then, the pile foundation is evaluated independently to obtain the equivalent stiffness; and these values are used in the interaction analysis. The spacing between the piles in a group is varied to evaluate its effect on the interactive behaviour of frame. Similarly, the effect of pile diameter is also evaluated on the response of the frame. The response of the frame included the displacement at the top of the frame and bending moment in columns. The effect of the soil-structure interaction is observed to be significant for the type of foundation and soil considered in the present study.